Quantifying Leaf Area Development Parameters for Cowpea [Vigna unguiculata (L.) Walpers]. Issue 6 (6th October 2016) - Hissene, Halimé Mahamat; Vadez, Vincent; Michelangeli, José Clavijo; Halilou, Oumarou; Ndoye, Ibrahima; Soltani, Afshin; Sinclair, Thomas
Abstract : Cowpea [ Vigna unguiculata (L.) Walpers] is a major crop legume for the Sahelian zone in Africa. An accurate simulation of the growth and yield for cowpea that considers the environment would be a robust tool for evaluating improved management and plant genetics. The objective of this study was to parameterize a simple model framework to describe cowpea leaf area development. To obtain field data in divergent environments, leaf area development was measured for four genotypes at two sites: Patancheru, India, and Bambey, Senegal. In addition, the effect of plant density was tested at Patancheru. Leaf area development was considered in two steps: the increase in main stem node number as a function of temperature (i.e., phyllochron) and plant leaf area as a function of main stem node number. The difference in phyllochron values among genotypes was not significant at Bambey, but one genotype at Patancheru significantly diverged from the others. Also, there was a plant density effect at Patancheru, especially for genotype Suvita‐2. An allometric power function, used to calculate plant leaf area based on the number of nodes, required two parameters: PLAPOW, the exponent in the function, and PLACON, the linear multiplier of the equation. Determination of the two parameters at Patancheru showed a genotype effect in both site and plant‐density effect. To examine the practical impact of genotypic differences and density effects in light interception and shading, estimated leaf development parameters were used to calculate light interception. There was very little variation in light interception resulting from the observed range in leaf phyllochron, PLAPOW, and PLACON and in density responses among the cowpea genotypes. The results of these experiments showed that, in most cases, a single set of parameters can be used to describe light interception by cowpea leaf canopies.